(untitled) (Eurasian Journal of History, Geography and Economics, 2024)
This article describes the role and development prospects of the Kashkadarya region in the oil and gas industry of Uzbekistan, the main oil and gas fields in the region, their production capacity and economic importance, as well as the development prospects of the oil refining industry and transport infrastructure. In addition, technological, ecological and infrastructure issues necessary to increase the potential of Kashkadarya region in the oil and gas industry, the future prospects of the oil and gas industry development and the need to ensure new technologies, investments and environmental safety in this process have been highlighted